The Process of Preparation for School in Foreign Countries and in Uzbekistan and its Main Issues - Тоrеmuratova Dilfuza Madenbaevna (International Journal on Orange Technologies, 2021)
The miraculous book of the Muslim world, the Qur'an, the Hadiths of Muhammad-alayhis-salom, the Avesta, and the perfect human education created by our scholars in their time, such as al-Beruni, al-Farabi, Abu Ali ibn Sina, and Alisher Navoi , their scientific-theoretical heritage of the issues of education has not lost its significance even today.